Pengaruh model pembelajaran problem-based learning (PBL) berbantuan media manipulatif terhadap hasil belajar matematika siswa kelas V sekolah dasar - Patoni, Muhammad Rijal; Ayu, Dya Ayu Agustiana Putri; Asriyanti, Frita Devi (Papanda Journal of Mathematics and Science Research, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model assisted by manipulative media on the mathematics learning outcomes of fifth grade students at SDN Bandung, Bandung District, Tulungagung Regency. This study is a type of quasi-experimental research (Quasi Experimental Design) with the Nonequivalent Control Group Design model. The subjects of the study were selected by Noneprobability sampling with a saturated sampling model. The sample taken was 20 students consisting of 10 students in the experimental class and 10 students in the control class. The data collection method was carried out using an objective test in the form of multiple choices. The validity test of the test instrument was carried out using product moment while the reliability test used cronbach alpha. The analysis prerequisite test consisted of a normality test and a homogeneity test. Data analysis used parametric statistical techniques, namely the One Way ANOVA test with the help of the SPSS application program version 22.00 for windows. The results of this study indicate that the Problem Based Learning (PBL) learning model assisted by manipulative media has a positive effect on student learning outcomes. The results of the study showed an influence on student learning outcomes after implementing the PBL model assisted by manipulative media. In addition, students also reported that the use of concrete media helped them understand concepts better because they could see the spatial structure in 3D. This is evidenced by the calculation of the average value of the experimental class post-test objective test of 70.0, higher than the average value of the control class post-test objective test of 63.5. The results of the One Way ANOVA test analysis on the test questions obtained a probability value at a significance level of 0.05, the Fcount value = 3.909> F0.05 (3; 10) of 3.71